Computational study on the influence of Coanda jet on airfoils: two-dimensional case - Djojodihardjo, Harijono; Abdul Hamid, Mohd Faisal (2012)
The influence of Coanda effect for lift generation and enhancement, following renewed interest elsewhere, is investigated using CFD simulation. To that end, attention is focussed on two-dimensional configuration and Coanda-Jet located at the trailing edge, to reveal the key elements that could exhibit the desired performance criteria for lift enhancement and drag reduction, or a combination of both. Parametric studies are carried out to obtain some optimum configuration, by varying pertinent airfoil geometrical and Coanda-Jet parameters. Particular attention is also given to turbulence modelling, by meticulous choice of appropriate turbulent models and scaling, commensurate with the grid generation, CFD code utilized and computational effectiveness. The present two-dimensional Coanda-Jet studies are carried out with wind turbine and micro-air-vehicle design in view.